El nivel de ejecución presupuestaria y su relación con subempleo en la macroregión selva durante el periodo 2007–2021 - Tuesta Chávez, Luis Paul (2025)
This study analyzes the relationship between budget execution, tax collection and working conditions in the Selva macroregion of Peru during the period 2007-2021. Using Spearman's correlation coefficient, the hypotheses linking these factors were evaluated, revealing significant findings. The research confirms a moderate negative relationship between budget execution and underemployment, suggesting that better management of public resources can reduce underemployment in the region. Furthermore, a strong positive correlation was found between tax collection and average income from work, indicating that greater formalization and tax efficiency contribute to improving labor income. Although the relationship between tax collection and unemployment is negative and significant, its is moderate, suggesting the need for complementary policies. Finally, an extremely strong relationship was observed between tax collection and budget execution, underscoring the importance of a robust fiscal system for effective public management. These results provide empirical evidence for the design of public policies that promote economic and social development in the Selva macroregion, highlighting the interdependence between efficient collection, effective budget execution and improvement of working conditions.